More than smart technology: a conceptual framework for Smart Countryside - Weith, Thomas; Prossek, Achim; Weddige, Ulf; Gütte, Annelie; Zscheischler, Jana (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
Up to now, there is no equivalent to the smart city concept for rural areas. Such a concept can draw on the findings and experiences from the urban context, but must adequately take into account the characteristics and structures of rural areas. This is where the enrolment of a concept for smart countryside in this paper starts as an action-oriented framework. Through an integrative consideration of current trends and tendencies, normative debates about equality and justice as well as possibilities in various fields of action, it includes development options that become possible through digitalisation and ‘smart’ implementation. Their realisation should be strongly demanddriven. The concept includes also governance processes and knowledge management, and the application of co-design approaches. Development potentials of digitalisation are seen beyond simple technology orientation. The concept of digitalisation presented here can contribute to a more comprehensive transformation of rural areas towards sustainability. It formulates a joint design mandate for politics, society and science.